Cardiovascular actions of rattlesnake bradykinin ([Val(1), Thr(6)] bradykinin) in the anesthetized South American rattlesnake Crotalus durissus terrificus - Galli, G. L. J.; Skovgaard, N.; Abe, Augusto Shinya; Taylor, E. W.; Conlon, J. M.; Wang, T. (Amer Physiological Soc, 2005)
Incubation of heat-denatured plasma from the rattlesnake Crotalus atrox with trypsin generated a bradykinin (BK) that contained two amino acid substitutions (Arg(1) --> Val and Ser(6) --> Thr) compared with mammalian BK. Bolus intra-arterial injections of synthetic rattlesnake BK (0.01-10 nmol/kg) into the anesthetized rattlesnake, Crotalus durissus terrificus, produced a pronounced and concentration-dependent increase in systemic vascular conductance (Gsys). This caused a fall in systemic arterial blood pressure (Psys) and an increase in blood flow. Heart rate and stroke volume also increased. This primary response was followed by a significant rise in Psys and pronounced tachycardia (secondary response). Pretreatment with N-G-nitro-L-arginine methyl ester reduced the NK-induced systemic vasodilatation, indicating that the effect is mediated through increased NO synthesis. The tachycardia associated with the late primary and secondary response to BK was abolished with propranolol and the systemic vasodilatation produced in the primary phase was also significantly attenuated by pretreatment, indicating that the responses are caused, at least in part, by release of cathecholamines and subsequent stimulation of beta-adrenergic receptors. In contrast, the pulmonary circulation was relatively unresponsive to BK.
Keywords: reptile; vasoactive kinin; catecholamines; nitric oxide; adrenergic receptor